The protest repertoire of the civil society through the press in the Spanish democratic transition - Méndez Muros, Sandra (Historia y Comunicación Social, 2014)
This paper presents a study on the protest repertoire used by the civil society during the Spanish democratic transition. Taking as axis the value/news of the repertoire on two private media published in Seville between November 1975 and June 1977, we use the content analysis to focus on social sectors, formats and levels of conflict. We conclude that the progressive reorientation of the mediated protest towards the dialogue and the partnership is a clear example of complementarity between the civil society and the press in the change process.
Keywords: Civil society; Spanish democratic transition; press; protest repertoire